Shoeless Joe and Black Betsy - Bildner, Phil (Simon & Schuster Books for Young Readers, 2002)
Shoeless Joe Jackson, said by some to be the greatest baseball player ever, goes into a hitting slump just before he is to start his minor league career, so he asks his friend to make him a special bat to help him hit.